Analisis Mobilisasi Dini Post Sectio Caesaria dengan Proses Penyembuhan Luka Operasi di Rumah Sakit Umum Ulfuadi Kota Binjai - Jeny Ersarika Sitepu; Riska Susanti Pasaribu; Ninsah Mandala Putri Sembiring (Jurnal Anestesi, 2024)
World Health Organization (WHO) data estimates that every year there are 230 million major caesarean section operations performed worldwide, one for every 25 people alive (Haynes, 2015). WHO recommends caesarean section operations for only around 10-15% of the number of births. WHO’s recommendation is certainly based on an analysis of the risks that arise due to caesarean section, both risks for the mother and the baby (Sudiharjani, 2014). In 2016, the demand for caesarean section was 50%, and currently more than 60% of pregnant women want caesarean section operations for various reasons. This study aims to conduct an Analysis of Early Mobilization Post-Caesarean Section With the Healing Process of Surgical Wounds at Ulfuadi General Hospital, Binjai City. The population in this study were all mothers who gave birth by caesarean section. The number of mothers who gave birth by caesarean section at Ulfuadi General Hospital, Binjai City was 135 people. The research sample was 43 people. Analysis of early mobilization with the process of healing post-section caesarean wounds. According to researchers, the results of this study indicate that by carrying out early mobilization, post-section caesarean patients can improve blood circulation which can help repair wound tissue better. The faster the post-section caesarean mother moves, the faster she can go home and the faster the wound heals. Wound healing is faster when compared to not doing early mobilization. The results of the chi-square test have a p value of 0.001 where the p value <0.05, it can be concluded that the Analysis of Early Mobilization Post-Cesarean Sectio with the Process of Healing Surgical Wounds at Ulfuadi General Hospital, Binjai City.